Continuous idea contribution in open innovation communities: The role of verbal persuasion from peers - Zhang, Jiacheng; Qi, Guijie; Song, Chunlin; Chen, Jiali (Frontiers in Psychology, 2022)
A core issue for the sustainability of online innovation communities is how to effectively incentivize participants’ continuous idea contributions. To resolve this challenge, scholars have explored a series of motivation factors from the psychological, social and functional perspectives, among which peer feedback has received much attention. However, existing work tended to summarize unstructured peer feedback text with structured proxies (e.g., amount, diversity or timeliness), which may mask the richness of the text. To fill this research gap, the current study, on the basis of creative self-efficacy theory, investigates the influence of feedback language use from peers, including emotional support (i.e., emotional approval and individualized consideration) and constructive feedback (i.e., cognitive stimulation and intellectual stimulation), on individuals’ continuous idea contributions. Using data from 15,649 users of a popular online innovation community, our results show that emotional support, especially emotional approval, positively affects members’ continuous contributions, and that the effect is stronger when the provider is of a higher status. However, individualized consideration does not seem to work. In addition, we also find support from cognitive stimulation with regard to the effect of constructive feedback, and intellectual stimulation exerts an effect only when the provider’s status is high. Overall, these findings extend the current research and offer practical guidelines to the online innovation community.